A Framework for Graceful Interaction : Applying Laban Effort Theory to Define Graceful Movement Quality - Wan Hashim, Wan Norizan; Md Noor, Nor Laila; Wan Adnan, Wan Adilah (2010)
Direct manipulation which was introduced in the 1990s has enriched the technological and intellectual landscape of Human Computer Interaction (HCI) where interaction style progresses from linguistic to manual interaction via graphical objects. The engagement that results in the direct manipulation activity gives rise to a new philosophy of graceful interaction. However, ever since the concept was introduced, the HCI literature does not exhibit much related work on graceful interaction. In this paper, we present a design framework for graceful interaction through the use of Laban effort theory to formalize graceful interaction design. This framework presents a theoretical proposition and practical characteristics to describe the movement qualities of graceful interaction. The framework invites and challenges interaction designers for the exploration of graceful towards aesthetic interaction.